Reducing Packaging Waste – Mechanical Characteristics and Network Parameters of the Gelatin-Based Thin Film for Cruciferous Vegetables Packaging - Filip Babić; Bojana Balanč; Nikola Milašinović (Journal of Engineering & Processing Management, 2018)
The role of the materials used for packaging is to protect innercontent from external, mostly negative, factors. Besides beingsafe, and with good mechanical properties, these materials needto align with other consumers' needs and demands, being bothattractive and authentic, while at the same time meetingecological requirements. Gelatin-based thin films are goodcandidates for production of semi-soft cup-shaped products thatcould be used for cruciferous vegetables packaging. These filmswere prepared by a simple solvent evaporation method. Preparedfilms were characterized by swelling study and their mechanicalproperties were investigated. The optical characteristics of thefilms were determined by optical microscopy revealing that thesesystems possess attractive clear and transparent gold-yellowishappearance with a smooth surface.
Keywords: Gelatin; Glycerol; Chamomile Tea Extract; Polymer Thin Films